Touch interaction with Google Glass – Is it suitable for older adults?. Issue 110 (February 2018) - Haesner, Marten; Wolf, Sebastian; Steinert, Anika; Steinhagen-Thiessen, Elisabeth
Highlights: Qualitative and quantitative measurements of feasibility, usability and acceptance were applied. High acceptance of Google Glass but performance difficulties and moderate usability issues. Older adults with cognitive impairment have more difficulties using Google Glasses. Need for a combination of initial training and long-term support. An integration in their own glasses is absolutely essential for long-term usage. Abstract: Cognitive, perceptual and motor skill changes may prevent older adults from successfully using modern technology. Google Glass possesses only a few buttons and seems to be overall intuitive. The present study aimed to assess the usability and acceptance of Google Glass with 30 older adults aged 65 years and over. The participants were asked to perform several standardized tasks and rate the usability. They experienced severe problems solving the tasks. Although Google Glass received only a marginal usability rating with an SUS score of 64.2 points, 60% of the participants rated the design as attractive, the handling as rather good and the complexity of the system as low. With a short training, even older adults with sensory and cognitive disabilities are able to use Google Glass. Recommendations for developers were derived from the study and are presented at the end of the article. They should be taken into account for the development of mobile applications for older adults using Google Glass.